RP-HPLC based analysis of different polyphenols in seven species of Carex L. (Cyperaceae Juss.) from West Bengal, India (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Rajak P, Ghosh A. 2022. RP-HPLC based analysis of different polyphenols in seven species of Carex L. (Cyperaceae Juss.) from West Bengal, India. Biodiversitas 23: 2329-2341. Carex L. is one of the important genera of the family Cyperaceae having immense ecological significance and probable therapeutic potentiality due to the presence of bioactive phytochemicals i.e. polyphenols. RP-HPLC (reversed-phase high-performance liquid chromatography) based evaluation of polyphenols concerned with the chemotaxonomy of this genus, was a fundament of reported research but the evaluation of its therapeutic possibilities are still an open field of research. In concerned with the above aim, phytochemical investigation was done by analyzing the seven species of Indian Carexto to evaluate polyphenols employing RP-HPLC. The above-mentioned analysis reveals differences in the presence as well as the amount of these marker phytochemical components compositions of each and every studied species of Carex. Total of nine polyphenols was used as standard among which, except coumaric acid, all of the polyphenols were detected in considerable amount in the studied species. Among these seven species, Carex stramentitia Boott ex Boeckeler and C. alopecuroides D. Don were found to contain a higher number of polyphenols. Gallic acid was quantified in the highest amount in C. baccans Nees. A higher amount of phloroglucinol was also detected in C. insignis Boott and C. baccans. Remarkably, biochanin A, a highly significant therapeutic phytochemical, was only observed in higher amounts in C. alopecuroides.